Perilaku Ibu Dalam Pemantauan Tumbuh Kembang Bayi di Era Digital di Desa Tri Jaya Kecamatan Sungai Bahar Jambi - Ucik Ariati; Debora Paninsari; Tia Mawati; Yusniati Lubis; Yustina Juniyanti (Malahayati Nursing Journal, 2025)
ABSTRACT Monitoring children's growth and development is one of the important aspects in ensuring that children grow up healthy, smart, and optimal. Good child development is the main foundation for children's physical, mental and social health in the future. The purpose of this study was to determine the behavior of mothers in monitoring infant growth and development in the digital era. The type of research used is quantitative using an analytical observational design research design with a cross sectional approach. This research was conducted in Tri Jaya Village, Sungai Bahar District, Jambi. The population in this study were all mothers who had children 0-12 months as many as 55 people. The technique of taking subjects using total sampling of 55 people. The data collection method used was to use questionnaires and observation sheets that were prepared to measure variables. Variables measured behavior and growth and development of children 0-12 months. The research data analysis was univariate and bivariate analysis with chi square test. The results of the study explained that there was a relationship between maternal behavior and infant growth and development in the digital era (P = 0.002),. The conclusion of this study is that there is a relationship between maternal behavior and infant growth and development in the digital era.  Keywords: Behavior, Growth and Development, Baby, Digital Era  ABSTRAK Pemantauan tumbuh kembang anak merupakan salah satu aspek penting dalam memastikan anak tumbuh sehat, cerdas, dan optimal. Tumbuh kembang anak yang baik menjadi fondasi utama bagi kesehatan fisik, mental, dan sosial anak di masa depan. Tujuan penelitian ini adalah untuk mengetahui perilaku ibu dalam pemantauan tumbuh kembang bayi di era digital. Jenis penelitian yang digunakan adalah kuantitatif dengan menggunakan desain penelitian desain observasional analitik dengan pendekatan cross sectional. Penelitian ini dilakukan di Desa Tri Jaya Kecamatan Sungai Bahar Jambi. Populasi dalam penelitian ini adalah seluruh Ibu yang memiliki anak 0-12 bulan sebanyak 55 orang. Teknik pengambilan subjek menggunakan total sampling sebanyak 55 orang. Metode pengumpulan data yang digunakan adalah dengan menggunakan kuesioner dan lembar observasi yang disusun untuk mengukur variabel. Variabel yang diukur perilaku dan tumbuh kembang anak 0-12 bulan. Analisa data penelitian adalah analisis univariat dan bivariat dengan uji chi square. Hasil penelitian menjelaskan bahwa terdapat hubungan perilaku ibu dengan tumbuh kembang bayi di era digital (P=0,002),. Kesimpulan penelitian ini adalah terdapat hubungan perilaku ibu dengan tumbuh kembang bayi di era digital.  Kata Kunci: Perilaku, Tumbuh Kembang, Bayi, Era Digital.